Accessing Deep Traps Distribution in FeS2‐Doped Organic Photovoltaics. Issue 4 (19th February 2023) - Sharma, Punit; Rana, Aniket; T., Abhijith; Suthar, Rakesh; Karak, Supravat
Abstract : Although doping has the potential to improve the performance of organic photovoltaic cells (OPVc), doping effects on charge transport, recombination, and energetic disorder are still obscure. Doping has two opposing effects: on the one hand, dopant ions create more trap centers, while free dopant‐induced charges fill deep states, potentially providing better performance. The optimum amount of dopants can considerably improve the performance of OPVc. Herein, the energetic distribution of trap states in P3HT: PC71 BM‐based OPVc doped with iron pyrite nanocubes (NCs) is reported. Using the reverse bias transient photocurrent (TPC) measurement, the energetic trap distributions with different doping conditions are studied. The photovoltaic characteristics and TPC phenomena of the OPVc greatly improve through doping. Variations in trap distributions with doping levels are analyzed to interpret the obtained trap density of states profiles. The light‐dependent current–voltage characteristics help to identify the presence of a less trap‐assisted recombination process in the optimum device. This study highlights the mechanism for performance improvement in devices with optimal doping of iron pyrite NCs. Abstract : Through reverse biasing conditions, the deep traps within the active layer are easily accessible. With the help of reverse bias, transient photocurrent technique allows us to probe the energetic distribution of localized trap states and charge dynamics within the solar cell.